Influence of IoT, Edge Computing, and Real-Time Analytics Systems on Optimizing Resource Management in the Indramayu Fisheries Industry - Utomo, Bekti; Setiawati, Rahmi; Vandika, Arnes Yuli (Westscience Press, 2024)
The fisheries industry in Indramayu faces challenges in optimizing resource management due to inefficiencies and a lack of technological integration. This study examines the influence of the Internet of Things (IoT), Edge Computing, and Real-Time Analytics Systems on resource management optimization in the fisheries sector. Using a quantitative approach, data were collected from 150 respondents and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that IoT has the most significant impact on resource management optimization, followed by Real-Time Analytics Systems and Edge Computing. The integration of these technologies demonstrates a synergistic effect, enabling real-time data collection, efficient processing, and actionable insights. These findings underscore the transformative potential of digital technologies in fostering sustainable and efficient resource utilization. Practical recommendations include investing in infrastructure, enhancing technical skills, and promoting technology adoption through policy support. This research contributes to the growing body of knowledge on digital transformation in resource-intensive industries.